Limitations associated with thermoregulation and cardiovascular research assessing laborers performing work in the heat. Issue 4 (7th February 2023) - Morrissey, Margaret C.; Langan, Sean P.; Brewer, Gabrielle J.; Struder, Jeb F.; Navarro, John S.; Nye, Megan N.; Casa, Douglas J.
Abstract: Purpose: To quantify the current literature and limitations associated with research examining thermoregulatory and cardiovascular strain in laborers working in the heat. Methods: PubMed, SCOPUS, and SPORTDiscus were searched for terms related to the cardiovascular system, heat stress, and physical work. Qualifying studies included adult participants (18–65 years old), a labor‐intensive environment or exercise protocol simulating a labor environment, a minimum duration of 120 min of physical work, and environmental heat stress (ambient temperature ≥26.0°C and ≥30% relative humidity). Studies included at least one of the following outcomes: pre‐ and peak physical work, core temperature, heart rate (HR), systolic blood pressure, diastolic blood pressure, HR variability, and rate pressure product. Results: Twenty‐one out of 1559 potential studies qualified from our search. There was a total of 598 participants (mean = 28 ± 50 participants per study, range = 4–238 participants per study), which included 51 females (8.5%) and 547 males (91.5%). Of the participants, 3.8% had cardiovascular risk factors (diabetes: n = 10; hypertension: n = 13) and 96.2% were characterized as "healthy". Fifty‐seven percent of the included studies were performed in a laboratory setting. Conclusions: Studies were predominantly in men (91.5%), laboratory settings (57%), and "healthy" individuals (96.2%). To advance equity in protection against occupational heat stress and better inform future heat safety recommendations to protect all workers, future studies must focus on addressing these limitations. Employers, supervisors, and other safety stakeholders should consider these limitations while implementing current heat safety recommendations.